FAKTOR-FAKTOR YANG MEMPENGARUHI DEVIDEND POLICY PADA PERUSAHAAN FOOD AND BEVERAGE - Clarentina, Viona; Setijaningsih, Herlin Tundjung (Jurnal Paradigma Akuntansi, 2025)
This study aims is to prove the effect of factors that affecting Dividend Policy of Food & Beverage companies. Sampling method used in this research is the purposive sampling method by finding 10 samples of Food & Beverage companies. This research was conducted by testing hypotheses on each variable that had been determined by performing multiple regression of panel data using the E-Views 12 software. The results from this study state that Liquidity have positive and significant influence on Dividend Policy. However, Profitability have negative and significant influence on Dividend Policy and Leverage have positive and non significant influence on Dividend Policy.